Code Switching Used by Cinta Laura and Maudy Ayunda on YouTube Channel - Kd Nadia Rahayu Wulandari; I Gde Agoes Caskara Surya Putra (PRASASTI: Journal of Linguistics, 2024)
Nowadays, in the bilingual community using two languages in the communication process is often happens and that is called code switching. This  study  concerned  code switching in Cinta laura and Maudy Ayunda’s utterances on Cinta Laura YouTube Channel. The aims of this study is to identify the types of code switching of Cinta Laura and Maudy Ayunda utterances and also the meaning of utterances by Cinta Laura and Maudy Ayunda regarding the types of code switching. A descriptive qualitative method is used for this study to analyzing the data collected from one content video containing code switching. The data were collected by observation method through watching, trancribing, note taking and also classifying the utterances. The results of the analysis shows that found 147 data with Intra-Sentential Switching 76 (52%), Inter-Sentential Switching 62 (42%), and Tag Switching 9 (6%). The dominant type of code switching used by Cinta Laura and Maudy Ayunda on YouTube Channel is Intra-Sentential Switching.